Daya Saing Usaha Kecil dan Menengah (UMKM) di bidang kuliner di Era Digital dengan Pemanfaatan QRIS - Oktaria Putri Adelia, Hersia; Nurjannah, Rahma; Puspita Sari, Cherly; Panorama, Maya (Indonesian Journal of Islamic Economics and Business, 2025)
In the midst of the rapid development of this digital age, technology has changed the way to communicate, especially in the culinary sector. The Indonesian Standard Quick Response Code (QRIS) comes as an effective digital payment solution, allowing micro, small, and medium enterprises (MSMEs) to conduct cashless transactions with just one QR code. QRIS implementation provides a number of benefits, including increased operational efficiency, transaction security, and expanded market reach. However, QRIS also faces several challenges, such as administrative costs, delays in fund disbursement, and low levels of digital literacy among businesses. To examine the impact of QRIS implementation on the competitiveness of culinary MSMEs, secondary data analysis from various reliable sources was conducted. The findings show that culinary MSMEs that use QRIS in the digital era are able to increase their sales and competitiveness.